ANALISIS KUALITATIF PENGUASAAN KOSAKATA SISWA SMP KELAS VIII DALAM PEMBELAJARAN BAHASA INDONESIA - Kurniawati, Heni; Suroso, Eko (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
This study aims to describe the level of vocabulary mastery of students in grade VIII H SMP Negeri 5 Cilacap and identify the linguistic aspects that most affect their ability to understand and use vocabulary appropriately. This study uses a qualitative descriptive approach with subjects of 32 students in grade VIII H for the 2024/2025 school year. Data was obtained through a multiple-choice test of 33 question items covering six aspects, namely word class, word meaning, meaning relationships, word forms (morphology), receptive mastery, and productive mastery. The results of the study showed that students’ vocabulary mastery was classified as a medium category, with a fairly striking variation between receptive and productive aspects. The receptive aspect showed the highest results because students understood words more easily in a concrete and familiar context, while the morphology and meaning relationships aspects were the aspects with the lowest level of mastery. The low achievement in the morphological aspect shows that students are not used to analyzing the internal structure of words and the relationships between lexical elements. Overall, the results of this study confirm that students’ vocabulary mastery is partial and not systematic, so vocabulary learning needs to be directed to contextual, exploratory, and metalinguistic awareness-based strategies. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan tingkat penguasaan kosakata siswa kelas VIII H SMP Negeri 5 Cilacap serta mengidentifikasi aspek-aspek kebahasaan yang paling memengaruhi kemampuan mereka dalam memahami dan menggunakan kosakata secara tepat. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan subjek sebanyak 32 siswa kelas VIII H tahun ajaran 2024/2025. Data diperoleh melalui tes pilihan ganda sebanyak 33 butir soal yang mencakup enam aspek, yaitu kelas kata, makna kata, hubungan makna, bentuk kata (morfologi), penguasaan reseptif, dan penguasaan produktif. Hasil penelitian menunjukkan bahwa penguasaan kosakata siswa tergolong kategori sedang, dengan variasi yang cukup mencolok antara aspek reseptif dan produktif. Aspek reseptif menunjukkan hasil tertinggi karena siswa lebih mudah memahami kata dalam konteks konkret dan familiar, sedangkan aspek morfologi dan hubungan makna merupakan aspek dengan tingkat penguasaan terendah. Rendahnya capaian pada aspek morfologi menunjukkan bahwa siswa belum terbiasa menganalisis struktur internal kata dan hubungan antarunsur leksikal. Secara keseluruhan, hasil penelitian ini menegaskan bahwa penguasaan kosakata siswa bersifat parsial dan belum sistematis, sehingga pembelajaran kosakata perlu diarahkan pada strategi kontekstual, eksploratif, dan berbasis kesadaran metabahasa.